Contextualising Chinese Migration to Africa. (December 2018) - Sullivan, Jonathan; Cheng, Jing
Who are 'the Chinese' in Africa? Why are they there? As China's engagement with African countries intensifies, and the size of the Chinese population in Africa increases, these questions have elicited substantial attention. Many attempts to provide answers, especially in the media and popular publications, are problematically based on uninformed stereotypes and undifferentiated notions of 'the Chinese', by implication a homogeneous group lacking contextualisation. Seeking to address such characterisations, this paper uses the digital communications of present and prospective Chinese migrants to provide a more nuanced picture of the motivations, preoccupations and migration experiences of private entrepreneurs and state-owned enterprise workers.